Evaluation and consumer acceptance of five tomato (Lycopersicon esculentum Mill) cultivars in Northern Region of Ghana - Dari, L; Nenguwo, N; Sefa, V Afari (Journal of Postharvest Technology, 2018)
Tomato (Lycopersicon esculentum Mill) is one of the most widely consumed vegetables in the world. It is a major horticultural crop with a global production of 153 million metric tonnes. Many landraces of tomato are used in the Northern Region of Ghana including “Burkina”, “Techiman” and “Wosowoso” with “Wosowoso” been the most grown within and around the Tamale Municipality. The seed however, are farmers own seeds and farmers prefer buying those seed because they are relatively cheap compared with the foreign seeds sold on the market. The aim of this study was to evaluate the quality and shelf-life performance of some selected tomato varieties in comparison with the local landrace commonly grown by farmers in the Northern region of Ghana. Seeds of “Wosowoso”, Popvriend, Tanga, Tengeru 1997 and Tengeru 2010 were nursed and transplanted onto a land area of 4 x 2 m2for each treatment in completely randomized design. All samples performed well agronomically except for Tengeru 97 and 2010 which showed signs of been attached by leaf curl disease. Farmers preferred Tengeru due to the fruit size and ease of seeds extraction regardless of the leaf curl disease. Eighty percent of consumers preferred Tanya for firmness and taste.